Thrombotic complications in patients with hereditary bleeding disorders - Franchini, Massimo (Thrombosis and Haemostasis, 2004)
Thromboses in patients with hereditary bleeding disorders are uncommon. However, in some cases, the co-existence of prothrombotic risk factors may increase the likelihood of developing thrombotic complications in such patients. This review summarizes the cases of thrombosis reported in the literature and analyzes the most important risk factors for thrombosis in patients with a congenital bleeding tendency. In particular we focus on central venous catheter (CVC)-associated thrombosis, on the thrombotic complications of coagulation factor concentrate therapy and on the presence of prothrom-botic gene mutations. Data were identified by searches of the published literature, including PubMed, references from reviews and abstracts from the most important meetings on this topic. In conclusion, there is increasing evidence that thrombotic complications in patients with hereditary bleeding disorders have a multifactorial pathogenesis, depending on exogenous (coagulation factor replacement therapy, CVC, HIV infection) and/or endogenous (prothrombotic gene mutations) risk factors.
Keywords: Bleeding disorders; hemophilia; thrombosis